Crestal sinus augmentation in a head back position: Retrospective case series - Yuhang Zhang; Chunyuan Zhang (Wolters Kluwer Medknow Publications, 2023)
Objectives: To evaluate the clinical efficacy of Crestal Sinus Augmentation (CSA) in a head back position (CSA-HBP) for maxillary sinus mucosa elevation. Materials and Methods: We enrolled 209 patients, 246 maxillary sinuses, 348 sites in this study. Complications, maxillary sinus mucosal perforation rate and cumulative survival rate (CSR) data were collected to evaluate the clinical efficacy of CSA-HBP. Maxillary sinus mucosal elevation height (EH) and new bone height (NH) were measured by cone-beam computerized tomography and standard periapical radiographs. The implantation sites of residual bone height (RBH) ≤5 mm and RBH >5 mm were marked as Groups A (n = 81) and B (n = 267), respectively. The implantation sites of the second and third molar sites were marked as Group C (n = 134), and the remaining sites were marked as Group D (n = 214). Results: The RBH before implant placement was 6.63 ± 2.10 mm (95% confidence interval [CI] 6.41- 6.85 mm). The mucosal EH was 4.04 ± 1.86 mm (95% CI 3.85 - 4.24 mm). The NH was 2.36 ± 1.20 mm (95% CI 3.85-4.24 mm). No other complications were found except three cases of postoperative swelling and one case of nasal blood secretions. The overall mucosal perforation rate was 1.44% (5/348, 95% CI 0.2%-2.7%) and the rate of RBH ≤ 5 mm (Group A) was 1.49% (2/134, 95% CI 0%-3.50%). The 8-year CSR was 99.71% (347/348, 95% CI 99.2%-100.0%). Mucosal EH and NH were higher in RBH ≤5 mm (Group A) than in RBH >5 mm (Group B) (P = 0.001 and P = 0.001, Mann-Whitney U-test). There were no significant differences in mucosal EH and perforation rate between second and third molar sites (Group C) and other sites (Group D) (P = 0.77, Mann-Whitney U-test, and P = 0.16, Yates' Chi-square independence test). Conclusions: CSA-HBP is a minimally invasive and reliable technique.